First-line therapy-stratified survival in BRAF-mutant melanoma: a retrospective multicenter analysis - Schilling, Bastian; Gebhardt, Christoffer; Hassel, Jessica C. (Cancer immunology immunotherapy, 2019)
Background: Inhibition of the mitogen-activated protein kinase (MAPK) pathway as well as programmed death 1 receptor (PD-1) blockade was shown to prolong overall survival (OS) in patients with advanced B-Raf proto-oncogene (BRAF)-mutant melanoma. However, due to the lack of head-to-head trials, it remains unclear if one of these therapeutic approaches should be preferred in first-line therapy. Here, we present a retrospective analysis comparing anti-PD-1 monotherapy with BRAF/MAPK/ERK kinase (MEK) combined inhibition used as first-line agents in a real-world clinical setting. Patients and methods: Clinical data, routine blood counts and lactate dehydrogenase (LDH) levels of 301 patients with unresectable or metastatic melanoma harboring an activating mutation in BRAF (V600E/K) were included. Of these, 106 received anti-PD-1 antibodies, while 195 patients were treated with a selective BRAF inhibitor combined with an MEK inhibitor as palliative first-line therapy. Patients were sub-grouped according to previously described predictive and prognostic markers. Results: OS was significantly longer in patients receiving anti-PD-1 monotherapy compared to patients receiving combined MAPK inhibitors. Subsequent therapies were comparable among these groups. The difference in OS was less pronounced in patients with high LDH levels and visceral metastatic spread. Conclusion: First-line treatment with a PD-1 blocking antibody might be associated with longer OS than first-line inhibition of the MAPK pathway in patients with advanced melanoma harboring mutant BRAF. These hypothesis-generating data need to be confirmed or rejected in prospective, randomized trials.
Gesehen am 07.10.2019